2014
DOI: 10.1371/journal.pntd.0003059
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Impact of Mass Drug Administration on the Development of Protective Immunity against Schistosoma haematobium

Abstract: Previous studies suggest that protective immunity against Schistosoma haematobium is primarily stimulated by antigens from dying worms. Praziquantel treatment kills adult worms, boosting antigen exposure and protective antibody levels. Current schistosomiasis control efforts use repeated mass drug administration (MDA) of praziquantel to reduce morbidity, and may also reduce transmission. The long-term impact of MDA upon protective immunity, and subsequent effects on infection dynamics, are not known. A stochas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…However, if immunity was longer-lived and MDA was assumed to reduce transmission, a large over-shoot in measured egg count was observed. This modelling work was supported by antibody data suggesting MDA and transmission reduction may disrupt the development of protective immunity or alter existing population immunity [ 5 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, if immunity was longer-lived and MDA was assumed to reduce transmission, a large over-shoot in measured egg count was observed. This modelling work was supported by antibody data suggesting MDA and transmission reduction may disrupt the development of protective immunity or alter existing population immunity [ 5 ].…”
Section: Discussionmentioning
confidence: 83%
“…While our results in this study are theoretical, the rationale behind them has a sound biological basis. Recent work by Mitchell et al [ 5 ] found that if protective immunity to schistosomiasis was short-lived, antibody levels declined to pre-intervention levels during or after MDA. However, if immunity was longer-lived and MDA was assumed to reduce transmission, a large over-shoot in measured egg count was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 It has been stated that MDA may reduce population immunity in the long term and if stopped can lead to large rebounds in egg counts. 10,11 Moreover, multiple rounds of MDA among school children have resulted in a reduced efficacy of PZQ which poses a threat to global MDA programs. 12 Parasitological cure depends on the treatment dose.…”
Section: Current Global Strategy-mda With Single Oral Dose Of 40 Mg/kmentioning
confidence: 99%
“…Mathematical modeling of disease dynamics has proved to be a useful tool in many human infections, in particular, to understand the transmission characteristics of parasitic diseases in order to develop and evaluate the effects of control programs, [7][8][9] and to make predictions on the effects of different intervention options, [10][11][12] also exploring control strategies targeted at high-risk behavioral groups. 13,14 Transmission models of schistosomiasis have been in existence since the 1960s.…”
Section: Introductionmentioning
confidence: 99%